The Song of Suffering, Reconciliation and Redemption: A New Critical Reading of “Sonny’s Blues” - Sigdel, Chandrika (Mindscape: A Journal of English & Cultural Studies, 2023)
This research paper examines the story “Sonny’s Blues” by James Baldwin that depicts the everlasting sorrows and sufferings of two black brothers residing in Harlem, New York. The omnipresent suffering is caused primarily by their African-American identity that leads toward the split between the brothers and ultimately fuels the intra-racial conflict in the black community as a whole. In addition, amid the never-ending troubles and deeper wounds of the black brothers, jazz music, i.e., Sonny’s blues is offered as a soother and a healer that erases their pains and sufferings, and as a thread that reconciles, reawakens, and redeems the whole black community. To analyze such familial and communal upheavals which have directly afflicted the lives of the major characters in the story and the crucial role that jazz music plays in it, this paper draws the theoretical reading from a literary movement called New Criticism that treats a text as an autonomous whole, developed by Cleanth Brooks, Allene Tate, John Crowe and others.